Spatial variability of soil bulk density and its controlling factors in an agricultural intensive area of Chengdu Plain, Southwest China - Shan LI; Qi-quan LI; Chang-quan WANG; Bing LI; Xue-song GAO; Yi-ding LI; De-yong WU (Journal of Integrative Agriculture, 2019)
Soil bulk density is a basic but important physic soil property related to soil porosity, soil moisture and hydraulic conductivity, which is crucial to soil quality assessment and land use management. In this study, we evaluated the spatial variability of soil bulk density in the 0–20, 20–40, 40–60 and 60–100 cm layers as well as its affecting factors in Southwest China's agricultural intensive area. Results indicated the mean value of surface soil bulk density (0–20 cm) was 1.26 g cm−3, significantly lower than that of subsoil (20–100 cm). No statistical difference existed among the subsoil with a mean soil bulk density of 1.54 g cm−3. Spatially, soil bulk density played a similar spatial pattern in soil profile, whereas obvious differences were found in details. The nugget effects for soil bulk density in the 0–20 and 20–40 cm layers were 27.22 and 27.02% while 12.06 and 3.46% in the 40–60 and 60–100 cm layers, respectively, gradually decreasing in the soil profile, indicating that the spatial variability of soil bulk density above 40 cm was affected by structural and random factors while dominated by structural factors under 40 cm. Soil organic matter was the controlling factor on the spatial variability of soil bulk density in each layer. Land use and elevation were another two dominated factor controlling the spatial variability of soil bulk density in the 0–20 and 40–60 cm layers, respectively. Soil genus was one of the dominated factors controlling the spatial variability of soil bulk below 40 cm.